VIOLÊNCIA OBSTÉTRICA E INVISIBILIDADE SOCIAL: UM DESAFIO PARA A SAÚDE PÚBLICA BRASILEIRA (CIPEEX, 2026)
ABSTRACTIntroduction: Obstetric violence is a violation of human rights that persists in healthcare services despite advances toward humanized childbirth. It manifests through physical, psychological, and institutional practices that disrespect women’s autonomy and especially affect vulnerable groups.Objective: To understand the profile and implications of obstetric violence in Brazil, highlighting its relation to gender, race, and class inequalities, in order to support public policies and practices that promote humanized childbirth.Methodology: A narrative and qualitative literature review was conducted in databases such as BVS, SciELO, PubMed, and CAPES Portal, considering studies published between 2020 and 2025 addressing obstetric violence and social inequalities.Results: The analysis of nine studies showed that obstetric violence takes physical, psychological, moral, and institutional forms, primarily affecting Black, Indigenous, adolescent, and low-educated women. Reported impacts include trauma, postpartum depression, anxiety, and breastfeeding difficulties. The authoritarian care model and lack of informed consent contribute to victims’ invisibility and weaken policies for addressing the issue.Conclusion: Obstetric violence is a structural and intersectional phenomenon that requires profound changes in training and care practices. It is essential to value women’s protagonism and adopt ethical and humanized approaches to ensure equity and respect for reproductive rights.
Keywords: violência obstétrica; enfermagem obstétrica; desigualdade social